The Influence of Teacher Working Group Activities on the Teachers’ Performance: A Quantitative Study in Public Elementary Schools in Pancur District Rembang Regency - Arifin, Mokhammad; Rasiman, Rasiman; Supandi, Supandi (FKIP - Universitas Riau, 2025)
Improving teacher performance is a central priority in strengthening the quality of elementary education. One strategic effort in Indonesia is through Teacher Working Group (KKG) programs, which serve as collaborative and reflective forums for professional development. However, empirical evidence is still required to confirm how these activities affect teacher performance. This study aims to examine the influence of Teacher Working Group activities on the performance of elementary school teachers in Pancur District, Rembang Regency. A quantitative approach with an ex post facto design was employed, involving 117 teachers selected through proportional random sampling. Data were collected using a validated Likert-scale questionnaire and analyzed through descriptive statistics, Pearson correlation, and simple linear regression with SPSS. The results revealed a very strong positive correlation between KKG activities and teacher performance (r = 0.869, p < 0.01). Regression analysis further showed that KKG activities significantly influenced teacher performance, explaining 75.6% of its variance (R² = 0.756, β = 0.942, p < 0.05). The study concludes that optimizing KKG is an effective strategy to enhance teacher professionalism and improve the quality of elementary education, particularly in semi-peripheral regions.